Current insights and prospects for the pathogenesis and treatment of clinical manifestations associated with Down syndrome through neurotransmitter, inflammatory, and oxidative stress pathways - Alasmari, Fawaz; Ahmad, Ashfaq; Alsanea, Sary; Hammad, Alaa M.; Al-Qerem, Walid (Frontiers in Pharmacology, 2025)
Individuals with Down syndrome exhibit various changes in the human body systems, including alterations in the ocular, neurological, and dermatological systems. Especially, preclinical and clinical studies have determined Down syndrome patients to possess reduced intellectual and cognition abilities, which neurobehavioral effects are associated with altered molecular markers in the brain. For instance, neuroinflammation and increased brain oxidative stress are reported in animals models of Down syndrome, and the reversal of those markers lead to positive effects. Dopaminergic and serotonergic neurons are altered in individuals with Down syndrome, with dopamine and serotonin secretion reduced and their transporters upregulated. Hence, blocking reuptake of dopamine and serotonin might improve Down syndrome behavioral impairments. Norepinephrine loss was observed in a mouse model of Down syndrome, and treatment with a β2 adrenergic receptor agonist improved behavioral symptoms. Moreover, targeting certain glutamatergic receptors, particularly in the hippocampus, might correct the glutamatergic dysfunction and altered behaviors. Inverse agonists or antagonists of GABAergic receptors suppress GABA’s inhibitory role, an effect associated with improved cognition behaviors in models of Down syndrome. Reports also suggest partial involvement of the histaminergic system in the impairment of memory function observed in Down syndrome. Finally, cholinergic system alteration has been reported, but the therapeutic role of its modulation needs further investigation. This review collects and reports multi-Omics Studies on Down syndrome, the crucial roles of inflammation, oxidative stress independently as well as role of oxidative stress in pregnancies with Down Syndrome and biomarkers of maternal diagnosis of Down syndrome. This review further explained the role of neurotransmitter pathways in Down syndrome pathogenesis, prognosis and therapeutic intervention for Down syndrome and future directions for interventions.